Pengembangan Konsentrator Oksigen Berbasis Empat Bahan Filtrasi Sebagai Solusi Inovatif Alat Bantu Pernafasan - Dekki Widiatmoko; Rachmat Setiawibawa; Rafi Maulana Al-Farizi; Mokhammad Syafaat; Eriski Prawira (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Amidst the Covid-19 pandemic, there has been a significant increase in the demand for oxygen. More people require oxygen cylinders, yet the supply is insufficient to meet the community's needs. Oxygen Concentrators have become an essential device capable of producing pure oxygen with a purity level reaching 95% through the application of Pressure Swing Adsorption (PSA) technology. The resulting ratio produced by the concentrator is 33.4% for synthetic zeolite, 30% for silica gel, 20% for natural zeolite, and 26.7% for activated carbon.